2002
DOI: 10.1097/00001756-200204160-00015
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of cerebrospinal fluid proteins in Alzheimer patients

Abstract: By comparing the CSF proteome between Alzheimer disease (AD) patients and controls it may be possible to identify proteins that play a role in the disease process and thus to study the pathogenesis of AD. We used mini-gel technology in a two-dimensional electrophoresis procedure, sensitive SYPRO Ruby staining and mass spectrometry for clinical screening of disease-influenced CSF proteins in 15 AD patients and 12 controls. The levels of six proteins and their isoforms, including proapolipoprotein, apolipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
131
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 20 publications
12
131
1
5
Order By: Relevance
“…Eleven of the 13 spots selected were found to represent eight different proteins (Table II) (see Supplemental Table 4S for peptide coverage maps). Interestingly four of these proteins have been shown to have altered levels in AD CSF, including ␣ 1 ␤-glycoprotein, prostaglandin D 2 synthase, cystatin C, and ␤ 2 -microglobulin (9,10,12). Consistent with previous studies, ␣ 1 ␤-glycoprotein is decreased in the CDR 0.5 group, whereas cystatin C and ␤ 2 -microglobulin are increased.…”
Section: Fig 3 Representative Gel Images and 3-d Representations Ofsupporting
confidence: 86%
See 1 more Smart Citation
“…Eleven of the 13 spots selected were found to represent eight different proteins (Table II) (see Supplemental Table 4S for peptide coverage maps). Interestingly four of these proteins have been shown to have altered levels in AD CSF, including ␣ 1 ␤-glycoprotein, prostaglandin D 2 synthase, cystatin C, and ␤ 2 -microglobulin (9,10,12). Consistent with previous studies, ␣ 1 ␤-glycoprotein is decreased in the CDR 0.5 group, whereas cystatin C and ␤ 2 -microglobulin are increased.…”
Section: Fig 3 Representative Gel Images and 3-d Representations Ofsupporting
confidence: 86%
“…Our results may clarify discrepancies among AD biomarker studies. Some studies have reported reduced levels of transthyretin in AD CSF (41)(42)(43)(44), whereas one study found no significant differences between AD and control groups (45), and one study has reported increased levels of transthyretin in the CSF of AD patients (9). A similar inconsistency was found with ubiquitin (increases (46 -48), no change (49), and decreases (9)).…”
Section: Fig 3 Representative Gel Images and 3-d Representations Ofmentioning
confidence: 93%
“…The excitatory amino acid transporter 2 showed oxidation in the AD brain [147]. In the CSF of patients with AD, decreased levels for apolipoproteins, retinol-binding protein, and transthyretin were detected [101,160]. Whereas Puchades et al [101] reported decreased levels for ApoE, Fukuyama et al [161] found increased levels for the protein in the CSF of AD patients.…”
Section: Synaptosomal and Transport Proteinsmentioning
confidence: 99%
“…Indeed, many increasingly more powerful yet complementary proteomics technologies have been leveled at CSF biomarker discovery in the past decade, including: variations of 2D gel electrophoresis [2,20,[22][23][24][25][26][27][28][29][30]; SELDI-TOF-MS [31][32][33][34]; offline LC -MALDI-TOF [35]; and LC-MS/MS with either isotopecoded affinity tags (ICAT) [36], Tandem Mass Tags [37] or iTRAQ (isobaric tag for relative and absolute quantification) [38,39]. These techniques have all been used successfully to identify candidate biomarkers because they provide accurate relative quantitative information between or among samples.…”
Section: Introductionmentioning
confidence: 99%